PRELIMINARY EVIDENCE ON EFFECTIVENESS OF RAKTDA (MA 321), AN AYURVEDIC SUPPLEMENT, FOR OPTIMUM MANAGEMENT OF ANAEMIA – A SHORT REVIEW (International Journal of Ayurveda and Pharma Research, 2021)
Despite multiple nutritional programmes and iron supplementation therapies adopted over the past 50 years, Anaemia remains a highly prevalent condition in India. The underlying pathogenesis associated with Anaemia includes not only nutritional deficiencies, but also the issues with optimum absorption, bioavailability of food nutrients, and assimilation of absorbed nutrients. The current review comprises preliminary evidence on Raktda (MA 321), an Ayurvedic supplement for adjuvant or monotherapy use in long term treatment of Anaemia. Raktda has a holistic combination of ingredients including Mandoor Bhasma, Kant Lauh Bhasma, Praval Pishti, Muktashukti Pishti, Giloy Sattva, Yashtimadhu, Shilajit, Amalaki and many other herbs traditionally useful for treating all types of Anaemia and its associated morbidities. The synergy of herbs in Raktda reinstates normal physiology by functioning at five different levels: Agni, Pitta Dosha, Rasa Dhatu, Rakta Dhatu, and Rasayana. A small sample study (n = 16) on Raktda has shown an increase in mean Hb% from 9.231 to 11.046 (paired t-value= 8.5475, SE = 0.212, p